Studi Teknis Kebutuhan Angkutan Antar Jemput Dalam Propinsi Kalimantan Selatan - Zainal Abidin (Universitas Muhammadiyah Surabaya, 2017)
This study aims to assess the needs of intercity passenger travel demandbetweenSyamsudin Noor Internationl Airport and districts cities in South Kalimantan Privince. Passenger transport in Syamsudin Noor Airport is currently served by Airport CityTaxi, Intercity Taxi and Motor. In general, transport services from and to the airport is still not satisfactory, so that the necessary alternative modes that can fulfill the Syamsudin Noor Airport user expectations.This study using stste preference method results the intercities passenger transport demand thatis possible to organize from Banjarmasin, Banjarbaru and Martapura ranks highest demand number. Other cities such as Pelaihari, Batulicin, Kotabaru and Amuntai occupies the next position. Whilethe other cities despite the relatively smaller amounts of demand but average is still more than 150 people per day. This study results the tariff forBEP rates in accordance with the closest distance to the farthest distance Rp. 20,000, - to Rp. 135.000, -. While passenger survey results forWTP is Rp. 50,000, - to Rp. 150.000, -. So that commercial rates can be considered in accordance with the public willingness to pay.